RELATIONSHIP OF BURNOUT LEVEL WITH NURSE CARING PERCEPTION IN EMERGENCY DEPARTMENTS - Nani Lestari; Etika Emaliyawati; Kurniawan Yudianto (Universitas Padjadjaran, 2021)
Emergency departments nurses are prone to burnout because they are dealing with emotional patients and families, and the number of visits is more than the number of nurses on duty. The purpose of this study was to identify the relationship between burnout levels and perceptions of caring for nurses in the emergency departments. The research design used a descriptive correlational. The research instrument used 2 questionnaires, namely the Maslach Burnout Inventory-Health Service Survey, to measure the level of burnout (low, medium, and high) and the Caring Behavior Inventory-24 to measure perceptions of caring (good and poor). The study population consisted of nurses in the Emergency Departments in Dr. Hasan Sadikin Bandung Hospital with a sample size using a total sampling technique of 50 nurses. Univariate analysis for each variable is presented with a frequency distribution table and bivariate analysis using the Rank Spearman test. The results showed that nurses’ burnout level was in a low category (60%), and the perception of nurses caring was in a good category (64%). The relationship test results obtained a negative correlation (p-value = 0.000; r = -0.607), which means that the higher the burnout level, the lower the caring perception that is owned. The study concludes that most nurses have a low level of burnout and a good perception of caring. Hospitals are advised to maintain or eliminate low burnout by carrying out a sharing program between nurses or counseling and maintaining good caring by conducting caring simulation training.